Silica-containing polyetherimide hybrid films based on methyltriethoxysilane as precursor of inorganic network. (July 2016) - Hamciuc, Corneliu; Hamciuc, Elena; Vlad-Bubulac, Tachita; Vlad, Stelian; Asandulesa, Mihai; Wolinska-Grabczyk, Aleksandra
Abstract: Polyetherimide hybrid films containing 5–40% silica were prepared through a sol-gel process and thermal imidization by using methyltriethoxysilane as precursor of the inorganic network and a poly(amic acid) resulting from polycondensation reaction of 2, 2-bis[4-(4-aminophenoxy)phenyl]propane with 2, 2-bis[(3, 4-dicarboxyphenoxy)phenyl]propane dianhydride. The properties of these films, morphology, water vapor sorption capacity, free surface energy, mechanical, thermal and electrical characteristics, were studied. The films exhibited good thermal stability, having an initial decomposition temperature above 470 °C and glass transition temperature in the range of 187–200 °C. They showed low dielectric constant and low dielectric loss in a large frequency field. Gas permeation tests using small molecules (He, N2, O2 and CO2 ) at 6 bar and 30 °C indicated that the hybrid films containing higher silica content showed higher permeability for all the tested gases.